EuReCa_Srbija 2014-2023 - Analysis of data on non-initiation of CPR in relation to the etiology of cardiac arrest (Journal Resuscitatio Balcanica, 2024)
Introduction: Cardiac arrest is one of the five leading causes of death in Europe. Timely recognition and application of cardiopulmonary resuscitation (CPR) significantly increase the chances of survival. It is necessary to better understand the reasons for not starting CPR, with the aim that their identification leads to the improvement of guidelines and an increase in survival rates. The Aim: The aim of this study is to analyze the data on the non-initiation of CPR in the context of the etiology of cardiac arrest. Material and Methods: The study included epidemiologic data on out-of-hospital cardiac arrest (OHCA) collected through questionnaires from the EuReCa, European Resuscitation Council (ERC) studies. The criterion for inclusion in the research was a OHCA treated by the emergency medical service (EMS). Pediatric patients were also included in the analysis. The created database consisted of information defined by the unique protocol of the EuReCa ONE study, for the period of October 1, 2014 to December 31, 2023. Results: We found a statistically significant correlation between Utstein and EuReCa etiology of cardiac arrest and the proportion of non-initiation of CPR in recorded cases (p
Keywords: OHCA; CPRm Eureca Serbia; Ethics CPR; Epidemiology CPR